The theranostic optimization of PSMA-GCK01 does not compromise the imaging characteristics of [99mTc]Tc-PSMA-GCK01 compared to dedicated diagnostic [99mTc]Tc-EDDA/HYNIC-iPSMA in prostate cancer - Mamlins, Eduards; Scharbert, Lara; Cardinale, Jens; Krotov, Maria; Winter, Erik; Rathke, Hendrik; Strodel, Birgit; Ankrah, Alfred O.; Sathekge, Mike; Haberkorn, Uwe; Kratochwil, Clemens; Giesel, Frederik L. (Molecular imaging & biology, 2023)
Radiolabeled PSMA-ligands play a major role in today’s nuclear medicine. Since approval of [177Lu]Lu-PSMA-617 for therapy of metastatic prostate cancer, availability of 177Lu became bottleneck of supply due to the high demand. Recently, a theranostic PSMA-ligand, PSMA-GCK01, was developed which can be labeled either diagnostically with 99mTc or therapeutically with 188Re with both nuclides available from well-known generator systems. This novel tracer might aid to overcome aforementioned supply limitations. In this investigation, the biodistribution and general imaging characteristics of [99mTc]Tc-PSMA-GCK01 were compared with the diagnostic reference compound [99mTc]Tc-EDDA/HYNIC-iPSMA in patients with advanced stage prostate cancer. In addition, the binding of both ligands to PSMA was analyzed at the molecular level using molecular docking.
Gesehen am 30.01.2024